please answer this question
![please answer this question class=](https://us-static.z-dn.net/files/dc8/ea1c184e8fd9a83ee901b64944ea2aef.jpg)
We have the given indefinite integral ;
[tex]{:\implies \quad \displaystyle \sf \int \dfrac{x+1}{x(xe^{x}+2)}dx}[/tex]
We will use substitution hence to solving this integral
Now , put ;
[tex]{:\implies \quad \sf e^{x}=u}[/tex]
So that :
[tex]{:\implies \quad \sf dx=\dfrac{du}{u}\quad and\quad log(u)=x}[/tex]
Now , putting the values in the integral , it can be written as ;
[tex]{:\implies \quad \displaystyle \sf \int \dfrac{log(u)+1}{log(u)\{ulog(u)+2\}}\times \dfrac{du}{u}}[/tex]
Now , we will again use substitution method for making the integral easy. So put ;
[tex]{:\implies \quad \displaystyle \sf ulog(u)+2=v}[/tex]
So that ;
[tex]{:\implies \quad \displaystyle \sf du=\dfrac{dv}{log(u)+1}\quad and\quad ulog(u)=v-2}[/tex]
Now , we have ;
[tex]{:\implies \quad \displaystyle \sf \int \dfrac{\cancel{\{log(u)+1\}}}{log(u)v}\times \dfrac{dv}{\cancel{\{log(u)+1\}}u}}[/tex]
[tex]{:\implies \quad \displaystyle \sf \int \dfrac{dv}{v\{ulog(u)\}}}[/tex]
Now , putting the value of ulog(u) = v - 2
[tex]{:\implies \quad \displaystyle \sf \int \dfrac{dv}{v(v-2)}}[/tex]
Now , using partial fraction decomposition , ths given integral can be further written as ;
[tex]{:\implies \quad \displaystyle \sf \dfrac{1}{2}\int \left(\dfrac{1}{v-2}-\dfrac{1}{v}\right)dv}[/tex]
Now ,as integrals follow distributive property. So ;
[tex]{:\implies \quad \displaystyle \sf \dfrac{1}{2}\left(\int \dfrac{1}{v-2}dv-\int \dfrac{1}{v}dv\right)}[/tex]
[tex]{:\implies \quad \displaystyle \sf \dfrac{1}{2}(log|v-2|-log|v|)+C}[/tex]
[tex]{:\implies \quad \displaystyle \sf \dfrac{1}{2}log\bigg|\dfrac{v-2}{v}\bigg| +C}[/tex]
Putting value of v ;
[tex]{:\implies \quad \displaystyle \sf \dfrac{1}{2}log\bigg|\dfrac{ulog(u)+2-2}{ulog(u)+2}\bigg| +C}[/tex]
Now, putting value of u ;
[tex]{:\implies \quad \displaystyle \sf \dfrac{1}{2}log\bigg|\dfrac{e^{x}log(e^{x})}{e^{x}log(e^{x})+2}\bigg| +C}[/tex]
[tex]{:\implies \quad \displaystyle \sf \dfrac{1}{2}log\bigg|\dfrac{xe^{x}}{xe^{x}+2}\bigg| +C}[/tex]
[tex]{:\implies \quad \therefore \displaystyle \underline{\underline{\int \bf \dfrac{x+1}{x(xe^{x}+2)}dx=\dfrac{1}{2}log\bigg|\dfrac{xe^{x}}{xe^{x}+2}\bigg| +C}}}[/tex]